UPAYA BALAI BESAR KONSERVASI SUMBER DAYA ALAM RIAU DALAM PENANGGULANGAN TINDAK PIDANA ILLEGAL LOGGING DI KAWASAN SUAKA MARGASATWA BUKIT RIMBANG DAN BUKIT BALING - Haryanto, Popo; Erdianto, Erdianto; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Forests have a very important position and role in supporting national development. The Constitution of the Republic of Indonesia of 1945 Article 33 paragraph (3) explains that "the earth and water and natural wealth contained therein are controlled by the state and used for the greatest prosperity of the people". Forest areas in Indonesia have a function as a conservation function; protected function; and production function. In general, all forests have the function of conservation, protection and production. Each forest area has different conditions according to the physical condition, topography, flora and fauna and biodiversity and ecosystem. In Indonesia, the three functions of the Forest Area have been established as the main function of the forest. which is intended by the main function is the main function carried by a forest. The practice of illegal logging not only takes place in the production forest area but also penetrates in protected forests and conservation areas. On the other hand, the current global era with its various modernization devices has provided relatively accessible accessibility. The practice of illegal logging has threatened the survival of mankind in theworld.This research aims to find out efforts to combat illegal logging in the Bukit Rimbang Wildlife Reserve and Bukit Baling which is the authority of the Riau Natural Resources Conservation Center in terms ofmaintaining and protecting conservation areas conducted based on field studies and interviews. This type of research is categorized into a sociological legal study that stems from factual events and problems that occur and grow in the midst of society.The resultsof this study there are three important things, namely pertama intends to unifytheextent of the efforts that have been made by the Riau Natural Resources Conservation Center in terms of tackling illegal logging in the Bukit Rimbang Wildlife Reserve and Bukit Baling. Second, what obstacles occur in efforts to combat illegal logging in the Bukit Rimbang Wildlife Reserve and Bukit Baling. Third, what steps can be taken to overcome the problem of illegal logging in the Bukit Rimbang Wildlife Reserve and Bukit Baling.Keywords: Effort, Countermeasures, Illegal Logging